Hello,

All the previous are correct

(x+2)²=(x+2)(x+2)(x+2)² = ?

There is a general formula : (a+b)²=a²+2ab+b²

I don't understand how you could do the previous ones and why you can't do these oO(2x+3)(x-2) = ?

(3y+2)(2y-3)= ?

In general :

(a+b)(c+d)=a(c+d) + b(c+d) = ac+ad+bc+bd

For the first one for example :

(2x+3)(x-2)=2x(x-2)+3(x-2)=2x²-4x+3x-6=2x²-x-6.

Now, try to do the second one.

When you go to factorise, always look for a common factor.The next section is about factorisation and I don't understand it at all, so all help is greatly appreciated :

If you have ab+cb, then the factorisation will beb(a+c)

5ab+2b= ?4pq+q= ?7ty+10y= ?= 3(3xz+5x²z = ?xz)+5x(xz)

11ab-7bc = ?p²+3p=p*p²+3p = ?p+3p

The same as above2x²+xy = ?

4p²+6pq = ?

² means that you multiply twice the same number.